Evangélicos e ditadura militar brasileira (1964-1985): o uso de memórias e representações no ensino de história - Menezes, Marcelo Lemos (2024)
The overflow of memories about the military dictatorship in Brazil has generated disputes and conflicts that have undoubtedly reached schools. Amid such embarrassments and challenges of the present, historians/teachers are driven to critically revisit their methods, content and approaches implemented in classrooms. Our work aims to contribute to the promotion of methodologies capable of directing teachers and students to an effective exercise of investigative practices on denialist memories and representations. Simultaneously, it presents tools and rational operations that can be used by students in their practical lives, providing expanded understanding of their realities. Furthermore, it is important for us to move to the center of the theme of the military dictatorship, other stories, memories and identities still neglected by many narratives that deal with the topic. It is in this sense that we invoke evangelical subjects in our research. Permeating their periodicals, their representations and memories, we place them not as a homogeneous religious group, as common sense sees them, but in their doctrinal and identity heterogeneities, which will prove to be responsible for substantiating different positions, retractions and memories. of the military coup of 1964. In times of the rise of evangelicalisms in Brazil and their respective representations in classrooms, it is essential that we understand the evangelical identities embraced by our students, but even as such identifications prove to be essential for the acceptance or refusal of content educational backgrounds.